Normative Masculinities in Fathering Practices - Šumskaitė, Lina (Socialinė teorija, empirija, politika ir praktika, 2014)
SummaryIn the article, there are analysed 30 semi-structured interviews conducted by the author in 2011–2013 with men aged 23–44 and having small children. The aim of the study was to analyse power relations in fathering practices created by normative masculinity. The study participants’ experiences are analysed by usingR. W. Connell’s concept of hegemonic masculinity and T. Coles’ concept of mosaic masculinity as well as the fatherhood models historically formed in the country.The survey has revealed that the normative masculinity conceptions prevailing in Lithuanian society are manifested out in the study participants’ fathering practices. Non-compliance to one feature of normative masculinity undermines their confidence in themselves and encourages men to highlight the other features of normative masculinity in fathering or to rethink the prevailing norms of masculinity and to search for alternative ways to secure confidence in themselves as men and fathers.Key words: normative masculinity, hegemonic masculinity, power relations, fathering